Is there any deixis here?: the analysis of deixis in a textbook of elementary school - Pertiwi, Canda Ayu Arum; Elfiyanto, Sonny ((JELE) Journal Of English Language and Education, 2023)
A language is a device of sounds and written symbols utilized by the humans of a particular country or area to communicate with each other. Pragmatics is a linguistic study that learns the listeners' interpretation. Deixis, which is applied in this research, is one of the pragmatic studies. The researcher used the descriptive qualitative method in this research. The data sourcing of this research is three descriptive texts adopted from a second-semester textbook for elementary school level entitled "Active Learning, Fun Exercise." The researcher used Yule's (1996) book as the theory about three types of deixis. As a result, the researcher found that there is 37-person deixis that appeared in the textbook. The first person was mentioned 13 times, 0 times for the second person, and 24 words in the third person appeared in the texts. Other information is that 27 words of spatial deixis were found, and 11 deictic expressions of temporal deixis appeared in the texts, while most of the deictic words written were in the third person "He"